Post-thaw ATP supplementation enhances cryoprotective effect of iodixanol in rat spermatozoa. Issue 1 (December 2016) - Kim, Suhee; Hooper, Sarah; Agca, Cansu; Agca, Yuksel
Abstract Background Successful cryopreservation of rat spermatozoa from various strains still remains a challenge. The objective of this study was to determine if combinations of OptiPrep™ (iodixanol) and adenosine 5′-triphosphate (ATP) can improve rat sperm function during the cryopreservation procedure. Methods Epididymal rat spermatozoa were frozen under different OptiPrep™ concentrations (0, 1, 2, 3 or 4 %) and were diluted with media supplemented with or without 2 mM ATP after thawing. Post-thaw sperm motility, acrosomal membrane integrity (AMI) and mitochondrial membrane potential (MMP) were then evaluated. In addition, the effect of different OptiPrep™ concentrations on fresh and cooled rat spermatozoa was tested via motility. Results There was no effect of OptiPrep™ on motility of fresh and cooled spermatozoa. The supplementation of 1 and 2 % OptiPrep™ increased motility of frozen spermatozoa at 10 min after thawing, while it did not improve motility of spermatozoa at 3 h after thawing in the absence of ATP. During incubation of thawed spermatozoa, the ATP addition protected time-dependent decrease in motility after thawing in OptiPrep™-treated samples. OptiPrep™ had no effect on AMI and MMP in frozen-thawed spermatozoa but combinations of OptiPrep™ and ATP improved MMP in frozen-thawed spermatozoa. Conclusions Iodixanol has cryoprotective effects during rat sperm freezing without any toxic effect. Moreover, the combinations of iodixanol and ATP have a beneficial role in maintaining function of frozen-thawed rat spermatozoa for long period of incubation post-thaw.